Methodological Criteria for Limiting General Equality Before the Law - Virabyan, Gevorg (Bulletin of Yerevan University C: Jurisprudence, 2025)
Methodological criteria for limiting general equality before the law. The aim of this study is to examine the universal methodological criteria for limiting general equality before the law based on the analysis of contemporary theoretical material from the perspective of the current concept of formal equality and its characteristic features developed in legal doctrine. In this regard, the general equality of all was chosen as the object of the study, while the subject was chosen the identification of the legal framework for its limitation in the context of the following questions, which have both theoretical and practical significance; what do we understand by universal equality? what do we understand by "rule" in the context of general equality? in what case can the limitation of general equality before the law be aimed at achieving a goal established by the Constitution of the Republic of Armenia? Through the generalization of the stated objectives and ways of solving them, the methodological criteria for limiting general equality before the law were presented as the final result, beyond which the limitation of universal equality before the law cannot be qualified as proportionate.
Keywords: formal equality; proportionality; legitimate goal; general equality; instrumental theory; right to judicial protection; limitation of a fundamental right; rule; objective law; a state governed by rule of law